Visit to Lushoto, CCAFS East Africa learning site - CGIAR Research Program on Climate Change, Agriculture and Food Security (2013)
On 6 -19 September 2014 The CGIAR Research program on Climate Change, Agriculture and Food Security (CCAFS) East Africa undertook a participatory action research monitoring and evaluation and backstopping of activities at the Lushoto, Tanzania learning site. Photos S.Kilungu (CCAFS)